High Sensitivity of SIRT3 Deficient Hearts to Ischemia-Reperfusion Is Associated with Mitochondrial Abnormalities - Parodi-Rullán, Rebecca M.; Chapa-Dubocq, Xavier; Rullán, Pedro J.; Jang, Sehwan; Javadov, Sabzali (Frontiers in Pharmacology, 2017)
Aim: Sirtuins are NAD+-dependent deacetylases that regulate cell metabolism through protein acetylation/deacetylation, and SIRT3 is the major deacetylase among mitochondrial isoforms. Here, we elucidated the possible role of acetylation of cyclophilin D, a key regulator of the mitochondrial permeability transition pore (mPTP), in mitochondria-mediated cardiac dysfunction induced by ischemia-reperfusion (IR) in wild type (WT) and SIRT3 knockout (SIRT3-/-) mice. Methods: Isolated and Langendorff-mode perfused hearts of WT and SIRT3-/- mice were subjected to 25-min global ischemia followed by 60-min of reperfusion in the presence or absence of the mPTP inhibitor, sanglifehrin A (SfA). Results: Analysis of mitochondrial sirtuins demonstrated that SIRT3 deficiency upregulated SIRT4 with no effect on SIRT5 expression. Hearts of SIRT3-/- mice exhibited significantly less recovery of cardiac function at the end of IR compared to WT mice. Intact (non-perfused) SIRT3-/- hearts exhibited an increased rate of Ca2+-induced swelling in mitochondria as an indicator of mPTP opening. However, there was no difference in mPTP opening and cyclophilin D acetylation between WT and SIRT3-/- hearts subjected to IR injury. Ca2+-stimulated H2O2 production was significantly higher in SIRT3-/- mitochondria that was prevented by SfA. Superoxide dismutase activity was lower in SIRT3-/- heart mitochondria subjected to IR which correlated with an increase in protein carbonylation. However, mitochondrial DNA integrity was not affected in SIRT3-/- hearts after IR. Conclusion: SIRT3 deficiency exacerbates cardiac dysfunction during post-ischemic recovery, and increases mPTP opening and ROS generation without oxidative damage to mitochondrial proteins and DNA.